2020
DOI: 10.3390/tropicalmed5020095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rapid Extraction Methods Coupled with a Recombinase Polymerase Amplification Assay for Point-of-Need Diagnosis of Post-Kala-Azar Dermal Leishmaniasis

Abstract: To detect Post-kala-azar leishmaniasis (PKDL) cases, several molecular methods with promising diagnostic efficacy have been developed that involve complicated and expensive DNA extraction methods, thus limiting their application in resource-poor settings. As an alternative, we evaluated two rapid DNA extraction methods and determined their impact on the detection of the parasite DNA using our newly developed recombinase polymerase amplification (RPA) assay. Skin samples were collected from suspected PKDL cases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Here of note, the recent xenodiagnoses study performed by Mondal et al showed high infectiousness of PKDL cases towards sterile sand flies which confers the presence of parasite in peripheral blood streams [ 28 ]. In addition to the variability in clinical samples, the disparate sensitivities are attributable to the different forms of PKDL cases [ 11 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here of note, the recent xenodiagnoses study performed by Mondal et al showed high infectiousness of PKDL cases towards sterile sand flies which confers the presence of parasite in peripheral blood streams [ 28 ]. In addition to the variability in clinical samples, the disparate sensitivities are attributable to the different forms of PKDL cases [ 11 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, blood samples from endemic controls were used to determine the specificity of the assays, whereas skin samples were collected from PKDL patients to determine the sensitivity. However, previous studies substantiated the specificity of the assays through using blood samples from non-VL participants [ 11 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic bead-based purification methods omit the need for a centrifugation step, but several pipetting steps are still essential and total hands-on time exceeds 60 min [34]. Recently, a simple one-step purification protocol was applied to the extraction nucleic acid of paratuberculosis from fecal samples [35], Leishmania from blood and skin [36,37], Ebola from saliva [38], and rabies from tissue samples [39]. This method combined detergents and heat for the lysis step and magnetic beads to capture the inhibitors.…”
Section: Equipment-free Nucleic Acid Amplificationmentioning
confidence: 99%
“…Finally, several of the articles in this issue provide exciting opportunities for integrating new strategic and methodological approaches to enhance One Health approaches. For instance, Chowdhury et al [ 9 ] focus on improving point-of-need diagnostics with new molecular methods for rapid detection of kala-azar leishmaniasis in resource-limited settings. Yeh et al [ 10 ] argue that genomic technologies may be able to track changes in distribution of NTDs such as schistosomiasis in the face of climate change, as well as elucidate shifting parasite-vector dynamics.…”
mentioning
confidence: 99%